Manejo integrado de nematoides das galhas em trigo - Lemes, Cláudia Fernanda Carraro (2021)
Wheat (Triticum aestivum) is one of the main crop options in the rotation and succession cropping system. The deposition of straw on the soil surface by this crop can improve soil quality by helping to control diseases and pests, such as phytonematoids as long as the genotypes are resistant to phytopathogens. Crop rotation and succession associated with biological control are important strategies for the management of root-knot nematodes. Thus, the objective of this study was to characterize the reaction of wheat genotypes to Meloidogyne javanica and Meloidogyne incognita and to evaluate the action of biological nematicides in the control of M. javanica in wheat crop and in wheat-soybean succession system, under greenhouse conditions. The results are presented and discussed separately in this document, in three chapters. Chapter 1: Characterization of the reaction of wheat genotypes to Meloidogyne javanica and Meloidogyne incognita. For M. javanica, 29 treatments were tested, of which 27 included the wheat genotypes and two controls of nematode susceptibility, tomato (Solanum lycopersicum cv. Santa Clara) and cucumber (Cucumis sativus cv. Caipira). For M. incognita, 12 treatments were evaluated, among them 11 wheat genotypes and one control of susceptibility, the okra plant (Abelmoschus esculentus cv. Santa cruz 47). The genotype TBIO Sossego showed resistance reaction to M. javanica. All other genotypes were susceptible to M. javanica and M. incognita. Chapter 2: Action of microbial nematicides applied via wheat seed treatment in the control of Meloidogyne javanica. Six microbiological nematicides were tested in seed treatment of IPR Catuara wheat for population suppression of M. javanica: Bacillus firmus, B. subtilis + B. licheniformis, B. subtilis, Pochonia chlamydosporia, Purpureocillium lilacinum and Trichoderma harzianum. The control consisted of wheat plants without seed treatment with and without nematode inoculation. B. firmus provided greater penetration of second-stage juveniles in the roots evaluated at ten days after inoculation. At the end of the experiment, the active principles that stood out regarding the population suppression of M. javanica were T. harzianum and B. subtilis + B. licheniformis. In the roots of plants treated with P. chlamydosporia, B. firmus and P. lilacinum, there was greater multiplication of the nematode. Chapter 3: Action of microbiological nematicides in the control of M. javanica in a wheat-soybean succession system. Two microbiological nematicides were tested in seed treatment of wheat IPR Catuara and soybean BMX Bonus IPRO for supression of M. javanica population. The treatments were B. firmus and P. chlamydosporia applied in seed treatment of wheat and soybean genotypes inoculated with the nematode, and the control without seed treatment, with and without nematode inoculation. The soybean grown in succession to wheat, in the same experimental units according to the corresponding seed treatment. The best result regarding the population suppression of M. javanica was observed when both crops received treatment based on P. chlamydosporia, which also promoted the development of the soybean root system.